Les Lettres-Ideogrammes de L’alphabet Francais Contemporain - Гунчик, Ірина Олексіївна; Рафф'є, Венсан; Hunchyk, Iryna O.; Raffier, Venіsent (Східноєвропейський національний університет імені Лесі Українки, 2015)
Dans l’article il s’agit des lettres-idéogrammes de l’alphabet français contemporain. On les analyse comme des signes ouverts et fermés pour l’étude détaillée du point de vue de l’idéographie. On les a classifiés en trois groupes d’après leur fermeture. Selon les résultats la plupart des lettres majuscules imprimées appartiennent au groupe “zéro”. Le groupe “un” ne constitue que les six signes graphiques. Et seulement une lettre “B” qui appartient au groupe “deux”. En étudiant l’alphabet français on analyse en détail les lettres-idéogrammes cela inclut leurs composantes. Букви-ідеограми в абетці французької мови розглядаються як відкриті та закриті знаки для більш детального дослідження з точки зору ідеографії. Розроблено класифікацію трьох груп літер за місцем їх закритості. За результатами дослідження, більшість великих друкованих літер належить до групи «0». Групу «1» складають шість графічних знаків, до групи «2» належить тільки одна буква «В». Детально аналізуються літери-ідеограми, включаючи їх складові частини. Основними елементами літери-знака є коло та лінії (горизонтальна, вертикальна й крива), стріла і хрест. Більша частина літер є відкритими, які показують відкриту систему французької мови. Створено класифікацію малих букв-ідеограм на рівні графічного елементу, а також розглянуто прагматичну функцію певних графем. The article is devoted to the letters-ideograms which function in modern French alphabet. They are considered as often and close signs for the more detailed analysis from the point of view of ideography. The classification of three groups of letters according to their closure has been worked out. According to the results most of printed capital letters belong to group “o”. Group “1” has only six graphic signs. Only one letter belongs to group “2” – letter B. While studying the French alphabet we make a detailed analysis of letters-ideograms, including their component parts. We note that the essential elements of a lettersign are: the circle, the horizontal line, the vertical line, the curve, the arrow and the cross. Most of the letters are open, which show the open system of the French language. In our research the classification of small letters-ideograms of the French alphabet on the level of a graphic element has been worked out and the pragmatic function of certain graphemes has been considered. The basis of small letters of the French alphabet is the graphic element and the description of pragmatic function of certain graphemes. We consider graphic signs as graphic objects which a person uses for the conventional replacement of the other object and which can concern the notion of an idea, syllable and sound. As to their essence small letters are letter signs that fulfill some functions: communicative, syntactic, system-forming and pragmatic. First attempts to determine the typological features of the graphemes of the French alphabet in order to study the scantily explored for the present communicative – pragmatic properties of this class of orthograms on the language level, that is script and ideography, have been made. Examining the monograms as ideographic signs and joining their pragmatic functions, our own four-level classification of the graphemes and ideograms for the common indication of a graphic element which is the basis of each group and gives the possibility to analyze French spelling from the point of view of ideography, has been worked out.
Letters-ideograms in Modern French Alphabet
Літери-ідеограми у сучасному французькому алфавіті
Keywords: grapheme; graphic sign; ideogram; letter; French alphabet; component part; closure; pragmatic function; графема; графічний знак; ідеограма; літера; французький алфавіт; складова частина; закритість; прагматична функція; graphème; signe graphique; idéogramme; lettre; alphabet français; composante; fermeture; fonction pragmatique